High-Temperature Superconductor Step-Edge Fabrication for the Implementation of RSFQ Circuits - Snetler, Lukas Hendrick (Stellenbosch : University of Stellenbosch, 2008)
Thesis (MScEng (Electrical and Electronic Engineering))--University of Stellenbosch, 2005.